Psychological factors on irrational financial decision making Case of day-of-the week anomaly - Brahmana, Rayenda Khresna; Hooy, Chee-Wooi; Zamri, Ahmad (Emeraldin Sight, 2012)
Purpose – This research aims to explore and explain the determinants of irrational financial decision making, especially the day-of-the week anomaly, by using psychological approach. Design/methodology/approach – As it is a conceptual paper, this research explores the psychological biases literature and links it to the day-of-the week anomaly. Using Ellis’ ABC (Activating Event, Belief, and Consequences) Model, the authors survey and classify the stimulant as the occasion that stimulates the psychological biases of investors, and these psychological biases will bring a consequence in behaviour which is irrationality in weekend effect. Findings – Adopting Ellis’ ABC model, the paper constructs a theoretical framework that link the psychological biases and day-of-the week anomaly. The theoretical model is also given as a proposed model for future empirical research. Research limitations/implications – This paper contributes to research by giving the theoretical model and its framework. The latter, future research can examine the proposed psychological biases as the determinant of day-of-the week anomaly empirically. Originality/value – This paper conceptually builds a framework and derives a proposed equation model linking the psychological biases (weather, moon, attention bias, heuristic bias, regret, and cognitive bias) to the day-of-the week anomaly.